Revealing the microstructure evolution and excellent ductility of near-α Ti–6Al–3Nb–2Zr–1Mo alloy via spark plasma sintering using pre-alloyed spherical powders - Yuting Hu; Yaming Shi; Yuqin Zhang; Yehua Jiang; Junsheng Wang (Journal of Materials Research and Technology, 2025)
Utilizing pre-alloyed spherical powders in powder metallurgy to prepare multi-component titanium alloys offers a promising strategy, which can improve energy transfer and microstructure uniformity and thereby achieve excellent mechanical properties. In this work, Ti–6Al–3Nb–2Zr–1Mo (Ti-6321) alloys were fabricated by spark plasma sintering (SPS) using pre-alloyed spherical powders. The effects of sintering temperature and powder particle sizes on the microstructure evolution, dislocation motion, and mechanical properties were systematically investigated. The results indicate that the microstructure changes from the martensite morphology of spherical powder at 875 °C to a mixture of α lamellae, fine equiaxed α grains, and β-phase particle chains at 900 °C, and then to coarse Widmanstätten microstructure at 925 °C. With the increase in sintering temperature, the elongation of Ti-6321 alloy shows an upward trend and then decreases, while the tensile strength remains relatively constant. Notably, the alloys exhibit excellent ductility (elongation ≥14.9%) and a certain level of tensile strength at 900 °C. This trend is consistent across alloys with powders of different particle sizes. Fundamentally, the certain strength and excellent ductility were attributed to two main factors. The plastic deformation of spherical powders promotes dislocation formation, while β phase particle chains obstruct dislocation motion, thereby maintaining alloy strength. Low-angle grain boundaries (LAGBs) that run through equiaxed grains provide movement channels for plugged dislocations, acting as carriers of plastic deformation by amplifying dislocation glide. This work offers valuable insights into efficient preparation of multi-component titanium alloys and a new approach to employing spherical powders composed of diverse particles.